Religious Extremism, Religiosity and Sympathy toward the Taliban among Students across Madrassas and Worldly Education Schools in Pakistan - Hanif, Saba (Terrorism and political violence, 2021)
The role of religious seminaries (madrassas) and mainstream schools in developing religious extremism and sympathy toward Taliban (the most dangerous militant group in Pakistan) has received little, if any, scholarly attention. This study has empirically investigated the role, if any, played by religious seminaries (madrassas) and mainstream schools in promoting religious extremism, and especially sympathy toward the Taliban. The study compared attitudes among secondary school students, on the one hand, and madrassa students, on the other, and found school type to be a strong predictor of religious extremism. On the whole, madrassa students tend to hold the most extreme views. However, an individual’s religiosity appears to increase the likelihood of them becoming a Taliban sympathizer, meaning that it is religiosity rather than school type that affects sympathy toward the Taliban. The findings of this study are in line with other recent research, namely that education amplifies frustrated ambitions among individuals who then find gratification in taking extremist attitudes and/or actions.